PROBLEMS OF X-RAY MAMMOLOGY MANPOWER TRAINING AND MANAGEMENT - N. I. Rozhkova (Вестник рентгенологии и радиологии, 2016)
The paper considers the issues of manpower training in X-ray mammology. It mentions staff shortage and no special training, which reduces the efficient activities of X-ray mammographic rooms, as well as shortage of training facilities and no unified educational programs within interdisciplinary integration, inadequate technical equipment in the training facilities, the lack of an accounting system for training higher- and mid-level health workers, as well as engineers. Emphasis is placed on that the educational programs must comply with the organizational forms of testing the specialists to be employed. The introduction of a continuous education system should be accelerated to rule out the decay period of specialists’ competence.